EFFECTIVENESS OF RECEIVABLES MANAGEMENT AT PT XYZ - Nico Gilbert Nathaniel Siagian; Syahyunan; Nisrul Irawati (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
Accounts receivable is commonly both the largest part of current assets and the total assets of the company. Therefore, the implementation of internal control of accounts receivable is very crucial. Accounts receivable are bills made related to either sales and services or the sale of other assets. The higher the sales volume, the greater the profit obtained. This is descriptive qualitative research which was conducted not to test a hypothesis, but describe the management of receivables at PT Kawasan Industri Medan Member of Danareksa. The research results indicate that an effective management of receivables is done by accelerating the delivery of invoices and completeness of billing documents as well as providing an easy payment process. These are the important keys in accelerating the payment of industrial tenants so that it will accelerate the cash flow, minimize uncollectible accounts and create a neat record of receivables between PT Kawasan Industri Medan Member of Danareksa and industrial tenants.